Association of a null allele of SPRN with variant Creutzfeldt–Jakob disease. Issue 12 (19th September 2008) - Beck, J A; Campbell, T A; Adamson, G; Poulter, M; Uphill, J B; Molou, E; Collinge, J; Mead, S
Abstract : Background: No susceptibility genes have been identified in human prion disase, apart from the prion protein gene ( PRNP ). The gene SPRN, encodes Shadoo (Sho, shadow of prion protein) which has protein homology and possible functional links with the prion protein. Methods: A genetic screen was carried out of the open reading frame of SPRN by direct sequencing in 522 patients with prion disease, including 107 with variant Creutzfeldt–Jakob disease (vCJD), and 861 healthy controls. Results: A common coding variant of SPRN, two further single nucleotide polymorphisms (SNPs) and three rare insertion or deletion variants were found. A single base-pair insertion at codon 46, predicted to cause a frameshift and potentially a novel protein, was found in two patients with vCJD but not in controls (p = 0.01). Two linked SNPs, one in intron 1 and the other a missense variant at codon 7, were associated with risk of sporadic CJD (p = 0.009). Conclusion: These data justify the functional genetic characterisation of SPRN and support the involvement of Shadoo in prion pathobiology.